2010
DOI: 10.1053/j.gastro.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fat Absorption and Effect of Sham Feeding on Postprandial Lipema

Abstract: Background and Aims Given the importance of postprandial hyperlipidemia to increase risk for atherosclerosis, in the present study, stable isotope-labeled meals were fed to healthy subjects (7 males and 3 females) to investigate the kinetics chylomicron synthesis and the impact of sensory exposure to lipid on metabolism. Methods Subjects performed 2, 24-hr inpatient studies which entailed consumption of a liquid formula evening meal containing 30g of oil (+13C2 triolein) on day 1. Breakfast (day 2) consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 54 publications
3
81
0
Order By: Relevance
“…Nevertheless, a recent study from our lab found that adult subjects who preferentially overeat high-fat foods were all obese individuals unable to detect LA properly during 3-AFC tests (32). Obesity also compromises the activation of the taste-evoked vagal reflex loop (i.e., tongue-NTS-blood axis; FIGURE 4), normally triggered by an oral fat stimulation and leading to early changes in the plasma TG levels (28,127,128,130). Indeed, the TG rise observed in overnightfasted lean individuals subjected to a brief oral exposure to LA (sip and spit procedure) is lacking in obese subjects (32).…”
Section: B Obesity Also Affects the Orosensory Detection Of Lipidsmentioning
confidence: 93%
“…Nevertheless, a recent study from our lab found that adult subjects who preferentially overeat high-fat foods were all obese individuals unable to detect LA properly during 3-AFC tests (32). Obesity also compromises the activation of the taste-evoked vagal reflex loop (i.e., tongue-NTS-blood axis; FIGURE 4), normally triggered by an oral fat stimulation and leading to early changes in the plasma TG levels (28,127,128,130). Indeed, the TG rise observed in overnightfasted lean individuals subjected to a brief oral exposure to LA (sip and spit procedure) is lacking in obese subjects (32).…”
Section: B Obesity Also Affects the Orosensory Detection Of Lipidsmentioning
confidence: 93%
“…It is now recognized that a significant portion of the previous evening meal's TG resides in the enterocyte for 4--16 h after the meal. 23 This lipid will enter the blood at the onset of the next meal---a phenomenon termed the 'second meal effect'. This effect can be reduced by subjects consuming a low-fat evening meal the night before the postprandial study, and such a scheme will maximize detection of the test meal entry.…”
Section: Research Subject Preparationmentioning
confidence: 99%
“…Capsules have been used to deliver tracer lipids, 23,43 but one study reported that the recovery of 13 C in breath was 10 times higher when the tracer was fed in the meal than in capsule form. 44 Many investigators have fed only a single isotope-containing meal and therefore measure the acute postprandial response to that meal.…”
Section: Quantity Of Isotope and The Food Vehiclementioning
confidence: 99%
See 2 more Smart Citations